Addressing Antimicrobial Resistance in Nepal: A Call for Collaborative Efforts - Khadka, Sitaram; Giri, Santoshi (Europasian Journal of Medical Sciences, 2025)
Being one of the most important discoveries of medical sciences, antibiotics are, no doubt, considered life-saving drugs. However, antimicrobial resistance (AMR) intimidates the advancement in medical science posing a substantial risk to lives. Currently, around 700,000 people die each year due to drug-resistant diseases that might reach up to 10 million deaths annually by 2050 if remain unchecked.2 It is also estimated that by 2030, AMR would force about 24 million people into extreme poverty. AMR is no longer a concern for the distant future but is a global pressing issue that requires immediate attention.3 WHO has declared AMR as one of the top 10 global public health threats facing humanity. AMR has been increasing alarmingly globally. Most bacterial pathogens have shown high resistance to the majority of first- and some second-line antibiotics.5 The Global Antimicrobial Resistance and Use Surveillance System (GLASS) report 2019 reported that Escherichia coli and Klebsiella pneumoniae causing UTIs showed 54.4% and 43.1% resistance to the first-line antibiotic cotrimoxazole and 43.1% and 36.4% for ciprofloxacin, the 2nd option drug respectively.